2020
DOI: 10.20965/ijat.2020.p0018
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Diamond-Coated Tools for Ball End Milling of Sintered Tungsten Carbide

Abstract: Sintered tungsten carbide which has high hardness and high heat resistance, has been widely used in molds and dies. Research on the development of a cutting technology for sintered tungsten carbide (sintered WC-Co alloy) has been pursued mainly with the use of a turning process. We focused on building an efficient milling method for sintered tungsten carbide by using diamond-coated ball end tools, and have investigated their basic properties under specific cutting conditions. This study extends our previous wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…For comparison, Suwa and co-workers have conducted cutting experiments with carbide ball end mills coated with CVD diamond of similar thickness (10 µm) [ 24 ]. When machining an identical carbide grade (WC-15Co, 3 µm WC size), the tool lasted only 68.1 m, using coating peel-off as tool life criteria [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For comparison, Suwa and co-workers have conducted cutting experiments with carbide ball end mills coated with CVD diamond of similar thickness (10 µm) [ 24 ]. When machining an identical carbide grade (WC-15Co, 3 µm WC size), the tool lasted only 68.1 m, using coating peel-off as tool life criteria [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, Suwa and co-workers have conducted cutting experiments with carbide ball end mills coated with CVD diamond of similar thickness (10 µm) [ 24 ]. When machining an identical carbide grade (WC-15Co, 3 µm WC size), the tool lasted only 68.1 m, using coating peel-off as tool life criteria [ 24 ]. Wang et al [ 16 ] presented a thorough study focusing on the tribological properties and comparison of the cutting performance of diamond coatings with different morphologies: MCD, SMCD (sub-microcrystalline diamond), NCD, and MCD/NCD multilayer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have been conducted on the service life and machinability of tools according to the diamond grain size, deposition method, cutting parameters, and cutting-edge shape of diamond-coated cutting tools [ 7 , 8 , 9 , 10 , 11 ]. Bian et al [ 7 ] closely analysed two coated tools in ductile mode machining of materials with high hardness and brittleness through a micro-milling experiment on ZrO 2 ceramic materials of normal crystalline and nanocrystalline-coated flat endmills.…”
Section: Introductionmentioning
confidence: 99%
“…However, the delamination of coating can occur faster with nanocrystalline coating. Suwa et al [ 9 ] investigated the cutting performance of a diamond-coated ball endmill for milling a sintered tungsten carbide with varying cobalt content. They also analysed the effect of the morphology of the cutting edge and found that a cutting edge with an S shape showed a better cutting performance than that with a straight shape.…”
Section: Introductionmentioning
confidence: 99%